Diet-microbiome coevolution: the core mechanism for semi-aquatic adaptation and cross-habitat niche coexistence of the web-footed shrew (Nectogale elegans) - Jiang, Jiayi; Zhou, Sibei; Song, Jia; Xia, Chongxie; Yang, Xuexiang; Yang, Kun; Li, Fengjun (Frontiers in Microbiology, 2025)
The adaptation of mammals to semi-aquatic niches represents a pivotal ecological transition, in which the coevolution of dietary specialization and gut microbiome is regarded as playing a fundamental role. However, the general mechanisms that link these traits to survival across habitats remain insufficiently investigated, particularly in small mammals with high metabolic constraints. Using the web-footed shrew (Nectogale elegans), a rare small mammal with extreme semi-aquatic specialization, this study supplements the understanding of host-microbe symbiosis in the process of small mammals adapting to new ecosystem. To address how diet facilitates semi-aquatic adaptation, we integrated benthic community surveys and dietary DNA metabarcoding. Our results showed that the web-footed shrew primarily utilizes benthic macroinvertebrates (Diptera, Ephemeroptera, and Trichoptera), consistent with the composition of local benthic biomass, and supplemented by Cypriniformes fish. Comparative analysis of DNA metabarcoding with sympatric terrestrial rodents further revealed that semi-aquatic shrews achieve niche differentiation through two complementary mechanisms: habitat partitioning (aquatic vs. terrestrial) and trophic level differentiation (secondary consumers of invertebrates vs. consumers of plants). This discovery extends niche theory, demonstrating how habitat-specific resource utilization shapes trophic stratification. Compared to the terrestrial group, the gut microbiome of the semi-aquatic shrew exhibited significant differences in both microbiome composition and functional potential: dominance of Proteobacteria and Firmicutes, reduced abundances of carbohydrate-active enzymes (CAZymes), as well as selective enrichment of genes involved in fatty acid metabolism. These results reflect the high-fat, high-protein niche of semi-aquatic shrews. Additionally, the seasonal stability of the microbiome of the semi-aquatic shrew mirrors the consistency of benthic resources, and maintaining metabolic homeostasis is key to long-term adaptation to fluctuating environments. Overall, this study demonstrates a framework for semi-aquatic adaptation in small mammals: dietary specialization drives niche differentiation, which in turn selects for gut microbiome adaptation, optimizing habitat-specific resource utilization. This research underscores the role of diet-microbiome coevolution in enabling semi-aquatic adaptation, offering novel insights into ecological niche differentiation and specialization mechanisms in small mammals.